Is increased positive end-expiratory pressure the culprit? Autoresuscitation in a 44-year-old man after prolonged cardiopulmonary resuscitation: a case report. (December 2016) - Hagmann, Henning; Oelmann, Katrin; Stangl, Robert; Michels, Guido
Abstract Background The phenomenon of autoresuscitation is rare, yet it is known to most emergency physicians. However, the pathophysiology of the delayed return of spontaneous circulation remains enigmatic. Among other causes hyperinflation of the lungs and excessively high positive end-expiratory pressure have been suggested, but reports including cardiopulmonary monitoring during cardiopulmonary resuscitation are scarce to support this hypothesis. Case presentation We report a case of autoresuscitation in a 44-year-old white man after 80 minutes of advanced cardiac life support accompanied by continuous capnometry and repeated evaluation by ultrasound and echocardiography. After prolonged cardiopulmonary resuscitation, refractory electromechanical dissociation on electrocardiogram and ventricular akinesis were recorded. In addition, a precipitous drop in end-tidal partial pressure of carbon dioxide was noted and cardiopulmonary resuscitation was discontinued. Five minutes after withdrawal of all supportive measures his breathing resumed and a perfusing rhythm ensued. Conclusions Understanding the underlying pathophysiology of autoresuscitation is hampered by a lack of reports including extensive cardiopulmonary monitoring during cardiopulmonary resuscitation in a preclinical setting. In this case, continuous capnometry was combined with repetitive ultrasound evaluation, which ruled out most assumed causes of autoresuscitation. Our observation of a rapid decline in end-tidal partial pressure of carbon dioxide supports the hypothesis of increased intrathoracic pressure. Continuous capnometry can be performed easily during cardiopulmonary resuscitation, also in a preclinical setting. Knowledge of the pathophysiologic mechanisms may lead to facile interventions to be incorporated into cardiopulmonary resuscitation algorithms. A drop in end-tidal partial pressure of carbon dioxide, for example, might prompt disconnection of the ventilation to allow left ventricular filling. Further reports and research on this topic are encouraged.